Marriage, schooling, and excess mortality in prime-age adults: Evidence from South Africa - Yamauchi, Futoshi (International Food Policy Research Institute, 2007)
The institution of marriage plays some role in determining one’s risk of exposure to HIV. Since the transmission of HIV in the population is mainly through sexual activity, avoiding infection depends on risk-avoiding behavior. Consistently, empirical results show that excess mortality is concentrated in not-yet married adults aged 20-39 among both men and women. Therefore, the choice of when and who to marry appears to be related to risk of exposure. The objective of this paper is to determine the effect that schooling has on HIV/AIDS excess mortality, using panel data from South Africa. This paper tests the hypothesis that schooling affects when and who one marries and thus impacts the risk of mortality from HIV/AIDS. The effect could be negative or positive. On the one hand, since educated agents have incentives to secure returns to their human capital in the future, more education implies earlier marriage, given that the marriage institution effectively decreases the HIV-related mortality risk. On the other hand, education increases the opportunity costs of marriage especially for women, who need to increase their time spent in the household. Thus, schooling may increase mortality risks due to the increased risk of HIV infection... Results show that schooling increases excess mortality among women, but not among men... In sum, schooling increases the opportunity cost of marriage for women, which delays marriage and increases their mortality risks in high HIV-prevalence societies, but has the opposite effect on men. Our analysis demonstrated the need to integrate our understandings of the marriage market, the labor market, schooling investments, and youth behavior to identify the determinants of AIDS-related excess mortality.